Shiga toxin-converting phages and the emergence of new pathogenic Escherichia coli: a world in motion - Tozzoli, Rosangela; Grande, Laura; Michelacci, Valeria; Ranieri, Paola; Maugliani, Antonella; Caprioli, Alfredo; Morabito, Stefano (Frontiers in Cellular and Infection Microbiology, 2014)
Shiga toxin (Stx)-producing Escherichia coli (STEC) are pathogenic E. coli causing diarrhea, hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS). STEC are characterized by a constellation of virulence factors additional to Stx and have long been regarded as capable to cause HC and HUS when possessing the ability of inducing the attaching and effacing (A/E) lesion to the enterocyte, although strains isolated from such severe infections sometimes lack this virulence feature. Interestingly, the capability to cause the A/E lesion is shared with another E. coli pathogroup, the Enteropathogenic E. coli (EPEC). In the very recent times, a different type of STEC broke the scene causing a shift in the paradigm for HUS-associated STEC. In 2011, a STEC O104:H4 caused a large outbreak with more than 800 HUS and 50 deaths. Such a strain presented the adhesion determinants of Enteroaggregative E. coli (EAggEC). We investigated the possibility that, besides STEC and EAggEC, other pathogenic E. coli could be susceptible to infection with stx-phages. A panel of stx2-phages obtained from STEC isolated from human disease was used to infect experimentally E. coli strains representing all the known pathogenic types, including both diarrheagenic E. coli (DEC) and extra-intestinal pathogenic E. coli (ExPEC). We observed that all the E. coli pathogroups used in the infection experiments were susceptible to the infection. Our results suggest that the stx2-phages used may not have specificity for E. coli adapted to the intestinal environment, at least in the conditions used. Additionally, we could only observe transient lysogens suggesting that the event of stable stx2-phage acquisition occurs rarely.